Mast Cells in Alveolar Septa of COVID-19 Patients: A Pathogenic Pathway That May Link Interstitial Edema to Immunothrombosis - Motta Junior, Jarbas da Silva; Miggiolaro, Anna Flavia Ribeiro dos Santos; Nagashima, Seigo; de Paula, Caroline Busatta Vaz; Baena, Cristina Pellegrino; Scharfstein, Julio; de Noronha, Lucia (Frontiers in Immunology, 2020)
It is currently believed that innate immunity is unable to prevent the spread of SARS-CoV-2 from the upper airways to the alveoli of high-risk groups of patients. SARS-CoV-2 replication in ACE-2-expressing pneumocytes can drive the diffuse alveolar injury through the cytokine storm and immunothrombosis by upregulating the transcription of chemokine/cytokines, unlike several other respiratory viruses. Here we report histopathological data showing that mast cell density and IL-4 tissue expression are markedly increased in post-mortem biopsies of COVID-19 patients (n=6). In contrast, we detected fewer mast cells and lower IL-4 tissue expression in the alveolar septa of H1N1-induced pneumonia (n=10) or control specimens (n=10). Although conceding that cytokine storms may also influence the dynamics of recruitment and maturation of mast cells in the injured alveolar micro-environment, our histopathological data raise the possibility that mast cells-driven microvascular leakage and IL-4-mediated vascular injury may reinforce the intra-alveolar hyaline membranes and alveolar-capillary immunothrombosis by enhancing the influx of plasma coagulative factors to the alveolar lumen and promoting endothelial cell's pro-inflammatory response.